Hubungan Tingkat Pengetahuan Ibu Post Partum dengan Baby Blues Syndrom berdasarkan Tingat Kecemasan di Rumah Sakit Marinir Cilandak Tahun 2022 - Nurcahya, Bunga (MPI Press, 2024)
Introduction: Baby Blues is a mild effect disorder syndrome that often appears in the first week after delivery peaks on the third to fifth day and attacks within 14 days after delivery. The causes of Baby Blues Syndrome according to Marmi (2012), namely hormonal changes, stress, breast milk not coming out, frustration, fatigue, lack of support from husband and family, fear of losing the baby, and boredom. Objectives: To find out the relationship between the level of knowledge of postpartum mothers and baby blues syndrome based on the level of anxiety at the Cilandak Marine Hospital in 2022. Method: This research is quantitative correlational research using a